Dhaka stress scale-adolescent: A scale for assessing psychosocial stressors among adolescents - Mullick, Mohammad S. I.; Algin, Sultana; Islam, Monirul; Phillipson, Adrian; Nahar, Jhunu S.; Morshed, Nahid Mahjabin; Chowdhury, Hafizur Rahman; Shahid, Selina Fatema Binte (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This study was aimed to produce a culturally validated scale to determine the presence of stressful life events among adolescents in Bangladesh, and formulate the relative life change units for each event. The study used qualitative research, including a focus group and questionnaire, and quantitative analysis in the validation process. Researchers first developed a provisional stress scale that was translated in Bangla through a translation exercise. Using an open-ended question along with this provisional scale on a school sample of 449 (228 rated on imagination and 221 on actual experience) adolescents, researchers developed Dhaka stress scale– adolescent with 56 items and predictive interpretation of the overall score was made. Content validity was found excellent as item level content validity index was around 1 and the scale level validity index was 0.93. The correlation coefficient was 0.72 between this scale and adolescent life events stress scale. For reliability, Cronbach’s alpha values were ranged from 0.83 to 0.97. The scale is simple to administer to assess stress in adolescents and usable in both clinical and research settings.